Dislocation–grain boundary interaction-based discrete dislocation dynamics modeling and its application to bicrystals with different misorientations. (1st January 2021) - Zhang, Xu; Lu, Songjiang; Zhang, Bo; Tian, Xiaobao; Kan, Qianhua; Kang, Guozheng
Highlights: A 3D dislocation dynamics framework for various grain boundary (GB) types by using a 'coarse-graining' method was established. The dislocation–GB interaction model considers both dislocation absorption and dislocation emission at GBs. The compression behavior of several bicrystalline nanopillars with large-angle GB was investigated. Abstract: Grain boundaries (GBs) have a significant influence on the mechanical properties of metallic materials. It has been a great challenge to describe dislocation interactions with various GBs. In the present article, a generalized dislocation–GB interaction model was constructed and then implemented in the three-dimensional multiscale discrete dislocation dynamics (DDD) framework. In the model, two dislocation–GB interaction mechanisms, i.e., dislocation absorption at GBs and dislocation emission from GBs, were considered. In order to make the dislocation–GB interaction model suitable for various GB types, a 'coarse-graining' approach was applied to deal with the process of dislocation absorption and emission. As the validations and applications of the proposed dislocation–GB interaction model, nanopillars containing a non-sigma large-angle GB and subjected to uniaxial compression were studied. The simulated results show that the bi-crystalline nanopillars possess a higher yield strength and flow stress, smaller stress-drop size than single-crystalline counterparts, which is consistent with earlier experimental observations in the literature. Afterward, the DDD simulation was employed to reveal the effect of GB misorientation on the mechanical responses of bicrystals with a large-angle-symmetric-tilt GB. Simulations indicate that the mechanical responses of bicrystals are affected by the GB structures and complex dislocation–dislocation and dislocation–GB interactions. In contrast, the dislocation absorption and emission events, as well as the evolution of resolved shear stress and dislocation density, do not depend on the GB misorientation angles or the GB strength (or the GB energy). Graphical Abstract: Image, graphical abstract